2002
DOI: 10.1021/ja0202098
|View full text |Cite
|
Sign up to set email alerts
|

A Reappraisal, Based on 31P NMR, of the Direct Coordination of a Metal Ion with the Phosphoryl Oxygen at the Cleavage Site of a Hammerhead Ribozyme

Abstract: It has been generally accepted, on the basis of kinetic studies with phosphorothioate-containing substrates and analyses by NMR spectroscopy, that a divalent metal ion interacts directly with the pro-Rp oxygen at the cleavage site in reactions catalyzed by hammerhead ribozymes. However, results of our recent kinetic studies (Zhou, D.-M.; Kumar, P. K. R.; Zhang. L. H.; Taira, K. J. Am. Chem. Soc. 1996, 118, 8969-8970. Yoshinari, K.; Taira, K. Nucleic Acids Res. 2000, 28, 1730-1742) demonstrated that a Cd(2+) io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 44 publications
3
28
0
Order By: Relevance
“…For the same P9 substitution but in a background of 10 mM Mg 2+ , Peracchi et al (1997) found an 8.8-fold increased K 1/2 for stimulating Cd 2+ . Metal coordination to the A9/G10.1 site in activity-inhibited constructs has also been spectroscopically measured, providing further support for the description of the A9 interaction as a ground-state interaction (Horton et al 1998;Hunsicker and DeRose 2000;Suzumura et al 2002;Vogt et al 2006). Additionally, in the present study, the K 1/2 values for Cd 2+ activity stimulation in the WT and S p constructs likely represent low estimates of the actual K 1/ 2 values in this ionic background.…”
Section: Resultssupporting
confidence: 70%
“…For the same P9 substitution but in a background of 10 mM Mg 2+ , Peracchi et al (1997) found an 8.8-fold increased K 1/2 for stimulating Cd 2+ . Metal coordination to the A9/G10.1 site in activity-inhibited constructs has also been spectroscopically measured, providing further support for the description of the A9 interaction as a ground-state interaction (Horton et al 1998;Hunsicker and DeRose 2000;Suzumura et al 2002;Vogt et al 2006). Additionally, in the present study, the K 1/2 values for Cd 2+ activity stimulation in the WT and S p constructs likely represent low estimates of the actual K 1/ 2 values in this ionic background.…”
Section: Resultssupporting
confidence: 70%
“…Also here, phosphorothioate studies helped to prove the coordination of divalent metal ions during catalysis [271,272]. resonance, respectively [274][275][276][277]. The catalytic activity of the hammerhead ribozyme was also shown to be in principle independent of divalent metal ions [278] 113 Cd NMR, which allow to observe both the RNA liganding sites and the metal ion simultaneously.…”
Section: Cadmium(ii)-rescue Experimentsmentioning
confidence: 87%
“…According to the HSAB (Hard and Soft, Acid and Base) rule [21], a reduction in the cleavage rate of a 'soft' thio-substituted substrate should be observed in the presence of 'hard' Mg 2+ cation (the thio effect), and restoration of a normal cleavage rate of a sulfur-containing substrate should occur in the presence of thiophilic cations such as Mn , in increasing order (the rescue effect). Analysis of these types of interaction led to a better understanding of the mechanistic aspects of the action of naturally occurring catalytic ribozymes: group I and II introns [22][23][24][25], the RNA subunit of RNase P [26,27], and the hammerhead ribozymes [18,[28][29][30]. The successful application of Pchiral phosphorothioates in those mechanistic studies prompted us to establish the role of phosphate groups in the catalytic core of deoxyribozyme [10][11][12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: +mentioning
confidence: 99%